A comprehensive insight on the main physiological biochemical and related genes expression changes during the development of superficial scald in “Yali” pear - He, Jingang; Feng, Yunxiao; Cheng, Yudou; Wang, Meng; Guan, Junfeng (Frontiers in Plant Science, 2022)
Superficial scald is a serious physiological disorder in ‘Yali’ pear (Pyrus bretschneideri Rehd. cv. Yali) after long-term cold storage. Changes in superficial scald, ethylene production, α-farnesene and phenylpropane metabolism with associated gene expression in ‘Yali’ pear treated with and without (control) 1-methylcyclopropene (1-MCP) were investigated. Compared with the control group (without 1-MCP), 1-MCP (1.0 μl L-1) significantly lowered the superficial scald index after 180 days of cold storage. During cold storage and shelf life, the contents of α-farnesene, conjugated trienols, chlorogenic acid and epicatechin in the peel were reduced，while quercetin was enhanced in 1-MCP-treated fruit, and the expression of genes associated with ethylene synthesis (ACS1, ACO1),receptors (ETR2, ERS1) and signal transduction (ERF1), α-farnesene metabolism(AFS1, HMGR2, GST7), phenolic biosynthesis (PAL1, C4H1, C4H2, HCT3, 4CL2, C3H) and oxidases (PPO1, PPO5 and LAC7) were significantly downregulated by 1-MCP. These results suggested that the onset and development of superficial scald was closely related to the ethylene receptor, conjugated trienols, chlorogenic acid and epicatechin and related genes expression in ‘Yali’ pear.